THE IMAGE OF CHINA IN PEARL BUCK’S WORKS: BETWEEN STEREOTYPE AND CULTURAL EMPATHY - Tukhtayeva Farida Ismatullayevna (Bright Mind Publishing, 2025)
This paper explores the duality of cultural representation in the works of Pearl S. Buck, focusing on how she constructs the image of China through a lens that balances stereotype and cultural empathy. Drawing on her personal experiences growing up in China, Buck offers nuanced depictions of Chinese society, particularly rural life, that challenge prevailing Western misconceptions. Her novels, notably The Good Earth, present Chinese characters with emotional depth and cultural authenticity, reflecting a rare empathy for the “other” in early 20th-century Western literature. However, the analysis also addresses the persistence of orientalist tropes and essentialist views within her narratives, which at times simplify or generalize complex cultural realities. By examining this tension, the paper evaluates Buck’s role as both a cultural bridge and a product of her own Western background, ultimately highlighting the significance of her contribution to cross-cultural understanding despite its inherent limitations.
Keywords: Orientalist tropes, essentialist views, cross-cultural understanding, cultural authenticity, emotional depth, misconceptions, rural life, cultural empathy